2005
DOI: 10.1103/physrevlett.94.240601
|View full text |Cite
|
Sign up to set email alerts
|

Passive Sliders on Fluctuating Surfaces: Strong-Clustering States

Abstract: We study the clustering properties of particles sliding downwards on a fluctuating surface evolving through the Kardar-Parisi-Zhang equation, a problem equivalent to passive scalars driven by a Burgers fluid. Monte Carlo simulations on a discrete version of the problem in one dimension reveal that particles cluster very strongly: the two point density correlation function scales with the system size with a scaling function which diverges at small argument. Analytic results are obtained for the Sinai problem of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…To find the latter, we simulated a surface with height field h(r, t) evolving according to KPZ dynamics, and evaluated the density using the equilibrium weight ρ(r, t) = e −βh(r,t) /Z. As shown in [10], the results with β = 4 agree with the autocorrelation function in the nonequilibrium system, apart from a numerical factor.…”
Section: The Density-density Correlation Functionmentioning
confidence: 76%
See 4 more Smart Citations
“…To find the latter, we simulated a surface with height field h(r, t) evolving according to KPZ dynamics, and evaluated the density using the equilibrium weight ρ(r, t) = e −βh(r,t) /Z. As shown in [10], the results with β = 4 agree with the autocorrelation function in the nonequilibrium system, apart from a numerical factor.…”
Section: The Density-density Correlation Functionmentioning
confidence: 76%
“…Does the phenomenon survive in higher dimensions? These questions will be addressed in a subsequent paper [16], where it will be shown that the steady state is of the SCS kind in all these cases, even though the degree of clustering differs from one case to another.…”
Section: Future Workmentioning
confidence: 97%
See 3 more Smart Citations